Disambiguasi dan Hiperbolik untuk Seorang Pendidik dalam Surat Al 'Ankabuut [29]:43, 44 yang harus Dipecahkan secara Metodologis dan Implementasikan dalam Kelas - Muhammad Fatih (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
This study aims to discuss the way an educator implements in the classroom by breaking down methodologically disambiguation and hyperbolic Surat Al 'Ankabuut [29]: 43,44. This research is a qualitative, empirical, comparative literature study. It is a type of education and theological research which is a process of helping navigate through experiences (from scripture). What practical advice can help guide the theological education process? Then, comparisons are made to study the larger unit of analysis. From the results of the discussion, it is concluded that: 1) Educators in implementing classroom learning activities must be able to break down methodologically through disambiguation and hyperbolicism as indicated in the letter Al 'Ankabuut [29]: 43,44, namely knowledge and faith. 2) Through this disambiguation and hyperbolicism, anyone (of course, must be knowledgeable and have faith) is able to understand how chaotic the curriculum currently being implemented in this country is.